Implementation Of Scrum And Laravel In The New Student Admission Information System At STMIK Mercusuar - Sumaryanto, Maulana Aprizqy; Sinnun, Ahmad (Sean Institute, 2024)
Every new academic year, universities conduct new student admissions as a primary activity. However, at the School of Management Informatics and Computer (STMIK) Mercusuar, this process still relies on Google Forms, which is less efficient and lacks flexibility. This study aims to design a new student admission information system by utilizing the Laravel framework and implementing the Scrum methodology. The system is expected to facilitate access to new student admission information, streamline the registration process, and ease the verification of documents and selection of prospective students. The data collection techniques used in this research include qualitative research methodologies, such as observation, interviews, and literature studies. Scrum is employed in the software development process, offering flexibility and adaptability. The development of this information system is intended to simplify the new student admission process for applicants and to assist the admissions officers in managing registration, document verification, and the selection of prospective students. The use of the Laravel framework and the implementation of the Scrum methodology also contribute to creating a reliable and efficient information system. Consequently, this information system is expected to improve the quality and success of new student admissions at STMIK Mercusuar.